Fiqh al-Hadis Etika Bisnis (Tinjauan Kesahihan dan Pemahaman) - Busra Febriyarni (Institut Agama Islam Negeri Curup, 2016)
Business ethics will have an important meaning in providing insight to the business world in the future. The phenomenon of developing of business ethics is not lately simply one because of demands of reality of atmosphere turn more deepened but because the behavior of the perpetrators is getting away from the majesty of moral values (ethics). Nowadays, it has expanded the realm of Islamic economic studies at various universities.In the Indonesian context, the presence of business ethics is very urgent to look at the reality of corruption, collusion, nepotism, monopoly and others are increasingly grow and spread. These practices are highly contrary to the ethics that have been inscribed the Prophet Muhammad., as al-Amin in affairs of commerce. Prophet teach some principles in commerce include: honest, not cheating, ban of “najasy” selling, ban of “ihtikar” or monopoly and the payment of wages before his sweat dries. When some of these principles have been implemented well, then good luck and blessing in business will be acquired in the world and in the hereafter. The fifth hadith in this researchare “maqbul”in quality or acceptable (“saheeh” and “hasan”). Keywords: Business Ethics, Hadith Truth, Hadis Comprehension